PENGEMBANGAN MODUL ALJABAR LINEAR UNTUK MAHASISWA PENDIDIKAN MATEMATIKA - Salasiyah, Cut Intan (Al-Khawarizmi, 2017)
This study aims to produce Linear Algebra module for mathematics education students. This type of research is research development (R & D) with Plomp development model. The Plomp development model consists of five phases, namely: initial investigation phase, design phase, realization/construction phase, test phase, evaluation, and revision, and implementation phase. This research was conducted on students of mathematics education program of FKIP Samudra State University. Instruments used are in the form of validation sheet, test sheet and the questionnaire. The results showed that the Linear Algebra module that has been developed already met the aspects of good module quality, namely: the feasibility test module, Linear Algebra module that has been developed is valid based on the expert assessment; effectiveness test, where Linear Algebra module has an impact on the level of mastery and understanding of students on good criteria; test of practicality, where the result of questionnaire of practicality analysis shows that the module that has been developed can be implemented and used by the students.